2021
DOI: 10.17649/tet.35.3.3361
|View full text |Cite
|
Sign up to set email alerts
|

Kialakulhatnak-e okos falvak az Abaúji térségben?

Abstract: Tanulmányunkban az Abaúji térségben folytatott kutatás eredményeire támaszkodva arra szeretnénk választ kapni, hogy egy halmozottan hátrányos helyzetű térségben, ahol a gazdasági és természettudományi innováció alacsony szintű, segíthet-e, és lehet-e a társadalmi innováció a változások motorja. A kérdés megválaszolásához először áttekintjük az okos városok szakirodalmát és azokat a „smart” modelleket, melyek támogatást adhatnak, vagy szóba jöhetnek a fejlesztések során. Ennek során különbséget teszünk a falvak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Zhong et al ( 2021) indicated infrastructure is one of the main factor which influence the peasants' reconstruction intention of rural settlements in Panxi area in China when rural settlement development is the key to solve rural poverty issue. According to Sikos and Szendi (2021), smart infrastructure is thought as an innovative way to improve the economy of disadvantaged rural area. Sapkota (2018) found that improving road transport, drinking water and irrigation infrastructure is quite beneficial for human wellbeing.…”
Section: Keyword Co-occurrence Analysismentioning
confidence: 99%
“…Zhong et al ( 2021) indicated infrastructure is one of the main factor which influence the peasants' reconstruction intention of rural settlements in Panxi area in China when rural settlement development is the key to solve rural poverty issue. According to Sikos and Szendi (2021), smart infrastructure is thought as an innovative way to improve the economy of disadvantaged rural area. Sapkota (2018) found that improving road transport, drinking water and irrigation infrastructure is quite beneficial for human wellbeing.…”
Section: Keyword Co-occurrence Analysismentioning
confidence: 99%
“…There is abundant supply of scientific studies about different smart city models (Haibullin, 2018), (Sikos & Szendi, 2021), (Sallai, 2019) some of them is system based (Lom & Přibyl, 2020), some of them sees citizen as sensors (Cano, et al, 2015), others focusing on motivating factors (Herrera & Fajardo, 2016) or the resilience (Baran, et al, 2022). Based on the literature, (Anthopoulos, et al, 2015), (Anthopoulos, et al, 2016), Anthopoulos collected smart city conceptualization models and aggregated them into groups according to their focuses, Architecture (Naphade, et al, 2011), Governance (Baron, 2012), Planning and management, Data and knowledge (Batty, et al, 2012),…”
Section: Smart City Benchmark Modelsmentioning
confidence: 99%